Repercussões do cuidar sobre a vida do profissional enfermeiro no contexto da oncologia - Silva, Ediane da (2020)
Introduction - According to the INCA, cancer is considered a multifactorial disease (a set of more than 100 diseases) due to a combination of genetic and environmental factors that act simultaneously and sequentially. Thus, the worker who works in this health sector is subject to occupational risk, which is the probability of suffering some damage during their professional activities. Nursing work in the care of hospitalized cancer patients is a constant presence, and provides a scenario of conflicting practices that can contribute to the illness of workers. Factors related to infrastructure deficiency, exhaustive workload, low pay, continually dealing with anguish situations, exasperation due to the conditions experienced in the work environment with the suffering and death of others. Objective - To know the associated factors and the possible consequent repercussions of the act of caring that can cause damage or affect the physical, psycho-emotional and family health of the nurse workers, during the care of the cancer patient. Methodology - Prospective, exploratory, descriptive research with a qualitative and quantitative approach, carried out at a public university hospital, which serves the city of Uberlândia, Minas Gerais. We surveyed 11 active nurses who provide direct assistance to cancer patients, who were interviewed using a data collection instrument, prepared with questions regarding the socio-demographic aspect; about the history of the physical condition of the participant and the interview itself, consisting of six questions. In the analysis of the data, the transcription of the interviews was carried out, being typed, tabulated and an exhaustive reading was performed. The data referring to the sociodemographic factors and history of the participant's physical condition, were presented descriptively, and in the form of a table. Qualitative data were collected from the interview questions and analyzed in the light of the Collective Subject Discourse method, through thematic analysis. Results - The survey was conducted with 11 nurses, predominantly female (91%); married marital status (82%), Catholic religion (82%), ethnicity (82%) are called whites; age group older than 40 years (55%); education, only graduation (73%); Nursing exercise time between 15 and 22 years (27%). Regarding housing (91%), they have their own home. As for the guiding questions of the research, they refer to the health status of the participants distributed as follows: the majority (73%) do not have pathological symptoms, 27% have physical and emotional health problems, with withdrawal and use of drugs. It is also observed that 27.5% have no symptoms, 27.5% have stress and the others have varied symptoms, corresponding to 9% each. Therefore, of the 11 participants (100%), only 03 (27%) did not present any type of the indicated symptoms. Consequences on the health of some professionals were evidenced, such as stress, depression, and some symptoms of physical pain such as headache and dizziness resulting from emotional factors. Final considerations - Caregivers need to be taken care of too. Thus, it is necessary to observe the symptomatology of nurses from the beginning so that it does not worsen when it reaches an exhaustive phase, as the wear starts without being perceived in its possible severity. The study demonstrated the repercussions of caring and the physical and psycho-emotional consequences for the subjects involved, pointing out back pain, depression, panic syndrome triggered by work wear and tear. People only give of themselves what they have and, for that, they need to have psychological support to remain intact in their work. Some participants revealed a temporary departure from the sector for drug treatments. However, it would be ideal not to be on leave if there were a work organization that included less workload and divided responsibilities so as not to overload in any sense.